Malaysias independence must be defended and aid Palestine liberation - Ahmad Irfan, Ikmal Hisham (UMPSA, 2022)
PAYA BESAR, 2 September 2022 - Malaysians must defend the country’s independence as this is one of the factors that help the liberation of Palestine.